2007
DOI: 10.1534/genetics.107.078212
|View full text |Cite
|
Sign up to set email alerts
|

Two Zinc-Cluster Transcription Factors Control Induction of Alternative Oxidase in Neurospora crassa

Abstract: The alternative oxidase transfers electrons from ubiquinol to molecular oxygen, providing a mechanism for bypassing the later steps of the standard cytochrome-mediated electron transport chain. The enzyme is found in an array of organisms and in many cases is known to be produced in response to perturbations of the standard chain. Alternative oxidase is encoded in the nucleus but functions in the inner mitochondrial membrane. This implies the existence of a retrograde regulation pathway for communicating from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 56 publications
2
46
0
Order By: Relevance
“…In N. crassa, electrophoretic mobility shift assays showed that AOD2 and AOD5 act synergistically to bind an alternative oxidase induction motif (AIM) present in the promoter of the aod-1 gene, which encodes the alternative oxidase. These data support the hypothesis that the two proteins interact with each other (Chae et al 2007b). The AIM motif consists of one pair of CGG repeats separated by 7 bp and is essential for the inducible expression of the aod-1 gene.…”
Section: G303ssupporting
confidence: 84%
See 2 more Smart Citations
“…In N. crassa, electrophoretic mobility shift assays showed that AOD2 and AOD5 act synergistically to bind an alternative oxidase induction motif (AIM) present in the promoter of the aod-1 gene, which encodes the alternative oxidase. These data support the hypothesis that the two proteins interact with each other (Chae et al 2007b). The AIM motif consists of one pair of CGG repeats separated by 7 bp and is essential for the inducible expression of the aod-1 gene.…”
Section: G303ssupporting
confidence: 84%
“…The rse2-1 gene was shown to contain a single T-to-G substitution changing a Tyr into an Asp codon at position 300. Sequence comparisons revealed that this protein is homologous to the recently reported AOD2 protein from N. crassa, which acts synergistically with another transcription factor of the zinc-cluster family, AOD5 (Chae et al 2007b). This prompted us to search by BLAST the homolog of this protein in the P. anserina genome.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…It was hypothesised that the motif, which consists of a pair of CGG repeats separated by 7 bp, might be recognised by a member of the zinc-cluster family of transcription factors that might activate aod-1 expression by binding to the sequence (Chae et al 2007a). Indeed, the aod-2 and aod-5 gene products have recently been identified as transcription factors of this family (Chae et al 2007b). It is worth noting that the induction motif present in the aod-1 gene of N. crassa was only conserved in other members of the fungal order Sordariales.…”
Section: Transcriptional Control Of Aox Genesmentioning
confidence: 99%
“…In plants, the alternative oxidase is present in some tissues or developmental stages and may also be induced in response to a variety of stresses (7)(8)(9). In most fungi, it is undetectable, or present at very low levels, under normal growth conditions but becomes expressed when the cytochrome respiratory chain is restricted by inhibitors such as antimycin, azoxystrobin, and cyanide or by mutations (10)(11)(12)(13). Under these conditions, the AOX bypasses respiratory complexes III and IV.…”
mentioning
confidence: 99%